PKM MELATIH KEMAMPUAN MOTORIK ANAK MELALUI PERMAINAN PUZZLE DAN LOMPAT TALI KB PAUD TUNAS CINDO DESA UPANG CERIA - Mella Libranti (Jurnal Abdimas Bina Bangsa, 2023)
This devotion aims to observe the motor skills of children at the Tunas Cindo KB PAUD Upang Ceria Village through jumping rope and puzzle games. This devotion is a qualitative service where the servant makes observations to observe the way teachers teach PAUD children to develop children's motor systems through jumping rope and puzzle games. This observation activity was carried out from February 1 2023 to February 28 2023, counting the 4 weeks this activity has been running. The first thing to do is to give an example to the child how to play jump rope and put together a puzzle and then ask the child to repeat as exemplified. Based on the results of the analysis of observations carried out over 4 weeks, it was found that teacher activity had an increasing tendency to carry out motor activity learning by carrying out regular physical games with explicit learning models and role playing models in jumping rope. game. Always increasing at every meeting from Meeting I, Meeting II, Meeting III to Meeting IV. Meeting I begins with the author observing how the teacher teaches the children, Meeting II with the writer giving examples to children of the rules in jumping rope and puzzle games, Meeting III with developing categories where children already understand and only 1 or two children who are still too active and violate the rules of the game, and Meeting IV the development is very good